Development of a Stair-Step Multifrequency Synchronized Excitation Signal for Fast Bioimpedance Spectroscopy. (19th February 2014) - Yang, Yuxiang; Bian, He; Du, Fangling; Sun, Qiang; Wen, He
Abstract : Wideband excitation signal with finite prominent harmonic components is desirable for fast bioimpedance spectroscopy (BIS) measurements. This work introduces a simple method to synthesize and realize a type of periodical stair-step multifrequency synchronized (MFS) signal. The Fourier series analysis shows that the p -order MFS signal f ( p, t ) has constant 81.06% energy distributed equally on its p 2 n th primary harmonics. The synthesis principle is described firstly and then two examples of the 4-order and 5-order MFS signals, f ( 4, t ) and f ( 5, t ), are synthesized. The method to implement the MFS waveform based on a field-programmable gate array (FPGA) and a digital to analog converter (DAC) is also presented. Both the number and the frequencies of the expected primary harmonics can be adjusted as needed. An impedance measurement experiment on a RC three-element equivalent model is performed, and results show acceptable precision, which validates the feasibility of the MFS excitation.